Process Simulation of Oil Palm Empty Fruit Bunch (OPEFB) Pyrolysis using Open-Source DWSIM: Analysis of Temperature-Dependent Product Yields - Utomo, Dani Puji; Andri Cahyo Kumoro; Muhammad Haqqiyuddin Robbani (Universitas Negeri Semarang, 2025)
This study investigates the pyrolysis of Oil Palm Empty Fruit Bunches (OPEFB) using the open-source process simulation software DWSIM to evaluate the impact of temperature on product distribution, particularly bio-oil, biochar, and pyrolysis gas. OPEFB, an abundant lignocellulosic waste from Indonesia’s palm oil industry, holds significant potential as a renewable biomass feedstock. The simulation model was developed based on thermochemical conversion principles and was validated against selected experimental data from the literature. Results show that pyrolysis temperature significantly influences the yield and composition of the products. The gas yield increased with temperature up to 460°C, dominated by CO, CO₂, and H₂ due to the decomposition of volatile organic matter. However, gas yield declined beyond 460°C, likely due to secondary reactions converting gas precursors into liquid products. The optimal temperature was found to be around 510°C, offering a balanced yield of bio-oil and gas with minimal biochar formation. The chemical composition of bio-oil included furfural, phenols, alcohols, and acetic acid—compounds derived from the breakdown of cellulose, hemicellulose, and lignin. Biochar yield decreased with temperature, but its quality improved in terms of carbon content and fixed carbon fraction. This study highlights the utility of DWSIM as an accessible and transparent tool for simulating biomass pyrolysis. Future work should focus on refining the kinetic parameters, experimental validation of simulation results, and integrating downstream processing for fuel and chemical recovery.